Relevansi Filsafat Dialektika Hegel pada Perang Diponegoro Tahun 1825-1830 - Mohamad Wildan Syamsu Dluha (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2021)
Philosophy is a science that we often hear and is one of the most basic sciences in life. Philosophy is the art of asking questions in life. The question posed by philosophy is unique because the aim is not to get an answer but to be able to explore other questions from the problem being asked. Various philosophical thoughts, one of which is the Dialectical Philosophy which was initiated by Georg Wilhelm Friedrich Hegel. This study uses a historical method consisting of heuristic stages, source criticism, interpretation and historiography. The results of the research show that the events of the Diponegoro War have relevance to Hegel's dialectical philosophy. This is reflected in the existence of thesis, synthesis and antithesis elements in the event. The interests of the Dutch led to royal resistance. The resistance is the people's response to inappropriate policies. This condition is called a thesis. This conflict also gave birth to a strategy of resistance tactics which was later called antithesis.